Studi Hadis di Kalangan Orientalis (Studi atas Pandangan Ignaz Goldziher dan Joseph Schacht): Hadith Studies among Orientalists (A Study of the Views of Ignaz Goldziher and Joseph Schacht) - Siti Humairah; Tanggareng, Tasmin; Farhah, Ummi (CV Kalimasada Group, 2025)
The purpose of this study is to analyze the views of orientalists in the study of Hadith, especially according to Goldziher and Schacht, and present a rebuttal to these opinions in order to create a balance in understanding the reading. Orientalism is often defined as Westerners studying the Eastern world. The orientalists in conducting Islamic studies, especially in studying the Hadith, are not all the same. In this paper, a literature review derived from several books related to the views of Hadith studies among Orientalists is used. As for the results of this paper on the views of Hadith studies among Orientalists according to Goldziher and Schacht, Orientalists are not all the same in viewing Islam. There are different opinions about Islam in the Hadith. This view is inseparable from how they judge the Prophet Muhammad because the Hadith is inseparable from everything related to the Prophet. In this paper, the author also adds a little rebuttal to the opinion in order to create a balance in reading comprehension.